Somatic aberrations of BRCA1 gene are associated with ALDH1, EGFR, and tumor progression in prostate cancer. Issue 3 (22nd October 2018) - Omari, Aleksandra; Nastały, Paulina; Stoupiec, Sara; Bałabas, Aneta; Dąbrowska, Michalina; Bielińska, Beata; Huss, Sebastian; Pantel, Klaus; Semjonow, Axel; Eltze, Elke; Brandt, Burkhard; Bednarz‐Knoll, Natalia
Abstract : BRCA1 is a pivotal tumor suppressor. Its dysfunction is known to play a role in different tumors. Among others, BRCA1 germline mutations account for higher risk and more aggressive course of prostate cancer (PCa). In addition, somatic BRCA1 gene loss was demonstrated to be a signature of PCa dissemination to lymph nodes and peripheral blood, and indicate worse clinical outcome. In order to substantiate the data for BRCA1 gene loss in PCa and reveal its phenotypical background, BRCA1 gene status was assessed in a large cohort of PCa patients and compared to different molecular factors. BRCA1 gene dosage was assessed in 2398 tumor samples from 1, 199 PCa patients using fluorescent in situ hybridization. It was compared to clinico‐pathological parameters, patients' outcome as well as selected proteins (Ki‐67, apoptosis marker, cytokeratins, vimentin, E‐ and N‐cadherin, ALDH1 and EGFR) examined immunohistochemically. BRCA1 losses were found in 10%, whereas gains appeared in 7% of 603 informative PCa patients. BRCA1 losses correlated to higher T stage ( p = 0.027), Gleason score ( p = 0.039), shorter time to biochemical recurrence in patients with Gleason score > 7 independently of other factors (multivariate analysis, p = 0.005) as well as expression of proteins regulating stemness and epithelial‐mesenchymal transition, that is, ALDH1 ( p = 0.021) and EGFR ( p = 0.011), respectively. BRCA1 gains correlated to shorter time to metastasis ( p = 0.012) and expression of ALDH1 ( p = 0.014). These results support the assumption that BRCA1 gene losses contribute to a progressive and stem cell‐like phenotype of PCa. Furthermore, they reveal that also BRCA1 gain conceivably representing loss‐of‐function might mark more invasive tumors. Abstract : What's new? Loss of the prominent tumor suppressor gene BRCA1 can be one signature of prostate cancer (PCa) aggressiveness and dissemination, with BRCA1 germline mutations, in particular, correlating to higher risk of occurrence and more aggressive course of PCa. Here, the authors substantiate in a large cohort of patients that somatic losses of BRCA1 gene present even in a small subpopulation of PCa cells might also indicate worse clinical outcome, stem‐cell like phenotype of PCa cells, and tumor progression. Hence, in the future, identification of BRCA1 gene aberrations might help to identify patients with the highest risk of metastasis and personalize therapy.